PENGARUH REALISASI BELANJA MODAL TERHADAP BELANJA DAERAH DI KECAMATAN SUKASARI BANDUNG PERIODE 2011 - 2016 - Hani Hatimatunnisani; Alen Dereas Putri (LPPM POLITEKNIK LP3I BANDUNG, 2018)
The study aimed to know the influence of realization capital expenditure to regional expenditure at Kecamatan Sukasari Bandung.The research method used a quantitative approach method. Data was analysed using simple linear regression models and t-test was employed to test the hypothesis with 5% level of significant. The results of the data showed that relationship realization capital expenditure and regional expenditure at Kecamatan Sukasari Bandung of 0,869 which means very strong with a coefficient of determination of 75,6% showed the influence of capital expenditure to regional expenditure and the remaining 24,4% is influenced by other factors. The problem that arise was that the late implementation of budget documents implementation of the regional work unit (DPA SKPD) and document implementation of budget changes (DPAP) on stucking on the process of activities to realize capital expenditure.The suggests given to the sub-district to have the attitude and a swift movement to provide intensive warning to the city government Bandung, and so also for the Bandung city government to quickly respond to warnings provided by the sub-district to accelerate the determination of DPA SKPD and DPAP for activities immediately realized